Sustainable poverty reduction in less-favoured areas - Ruben, Ruerd; Pender, John L.; Kuyvenhoven, Arie (CAB International, 2007)
Less-favoured areas with limited agricultural potential or difficult access conditions, support 40 percent of the world's rural population suffering from chronic poverty. While agricultural innovations and rural development programs have begun to be implemented within developing countries, they do not address the specific obstacles faced by this large population. Instead, a targeted approach is needed to identify different resource management strategies for particular types of households and communities as well as creating balanced investments aimed at sustainable intensification of rural livelihoods. Such efforts have been the focus of the research program on Regional Food Security Policies for Natural Resource Management and Sustainable Economies (RESPONSE). Through the study of less-favoured areas in Africa, Latin America, and South and East Asia, development pathways allowing for the careful adjustment of resource use strategies at the field, farm-household and village level are explored.